Case Report: Early-onset or recalcitrant cytopenias as presenting manifestations of activated PI3Kδ syndrome - Remiker, Allison S.; Lopes, Joao Pedro Matias; Jesudas, Rohith; Superdock, Alexandra; Park, Nami; Pateva, Irina (Frontiers in Pediatrics, 2024)
Background: Patients with recurrent, chronic, or refractory cytopenias represent a challenging subgroup that may harbor an underlying diagnosis, such as an inborn error of immunity (IEI). Patients with IEIs such as activated phosphoinositide 3-kinase delta syndrome (APDS) frequently have hematologic manifestations, but these are not often reported as presenting symptoms. As a result, IEIs may be overlooked in patients with early and/or recalcitrant cytopenias. Here, we describe the diagnostic journey and management of 3 patients that presented to a pediatric hematologist/oncologist with early onset or recalcitrant cytopenias and were diagnosed with APDS. Case presentations: Patients presented with early onset and/or refractory cytopenias. Two of the 3 patients developed multilineage cytopenias. Prior to an APDS diagnosis, 2/3 patients collectively underwent approximately 20 procedures that included biopsies, invasive endoscopies, and imaging; 1 patient had 8 differential diagnoses that were ruled out via additional testing. Along with recalcitrant cytopenias, a history of infections, and family history of lymphoproliferation, infections, or autoimmunity resulted in suspicion of underlying IEI and genetic testing. Genetic testing identified a pathogenic variant in PIK3CD in each patient, resulting in APDS diagnoses. Following diagnosis, 2 patients underwent changes in management of care with administration of intravenous immunoglobulin therapy (IVIG), the mTOR inhibitor sirolimus, or surgical procedures. These changes in treatment either improved or resolved cytopenias. The third patient experienced improvements in immune thrombocytopenia 1 month prior to his definitive diagnosis with IVIG. Following diagnosis, additional family members were also diagnosed with APDS due to follow-up genetic testing. Conclusions: These cases highlight the importance of early genetic evaluation in patients with early onset or recalcitrant cytopenias and demonstrate challenges in differential diagnosis. Additionally, the cases demonstrate beneficial changes in management and outcomes that can follow a definitive diagnosis, including the identification of targeted treatment options. Collectively, this case series supports the notion that underlying IEIs should be considered in the workup of early onset or recalcitrant cytopenias, particularly in patients who present with a combination of hematologic and immunologic manifestations that are refractory to treatment, manifest at an unusually young age, or can be tied to family history.